Encyclopedia of the Age of Political Revolutions and New Ideologies, 1760-1815. - Welton, Ann (Booklist, 2008)
Reviews the book "Encyclopedia of the Age of Political Revolutions and New Ideologies, 1760-1815" by Gregory Fremont-Barnes